Penyelesaian Ganti Rugi Lahan yang Terdampak Proyek Pembangunan Jalan Tol Solo-Yogyakarta di Pengadilan Negeri Klaten - Kurnianingsih, Marisa; Sartanto, Alfath; Sukirman, Anindhita Nurfaatin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
National strategic projects that are being intensively carried out by the government do not escape the emergence of disputes or disputes. This study raises the case of compensation due to the construction of expressway infrastructure or the Solo-Yogyakarta toll road, precisely in the Klaten area, which is experiencing problems, one of which is the determination of the compensation value for the affected community. The matter was brought to trial at the Klaten District Court with a fast-paced trial process carried out by the Panel of Judges. This research was structured using the juridical-empirical method. This study will describe the settlement of compensation for land affected by the Solo-Yogyakarta toll road at the Klaten District Court and explore facts to find out the obstacles experienced from the perspective of the applicant in the settlement of compensation for land affected by the Solo-Yogyakarta toll road.